Energy Efficient, Data Centric Routing Algorithm In Mobile Wireless Sensor Nodes (Energy Savings Quantification) - Nazeer, Mohammed; Murthy, Garimella Rama (International Journal of Computer Sciences and Engineering, 2025)
In this paper, we quantitatively (mathematically) reason the energy savings achieved in a wireless sensor grid network, by using circular leveling and sectoring routing algorithm. Due to the energy constraints on the sensor nodes (in terms of transmission and reception of energy) energy awareness has become crucial in sensor network. We provide analytical expression for the energy wastage that occurs when traditional Data Centric routing algorithm such as Direct Diffusion is utilized. Analytical results are validated through simulation, in NS2 simulator which shows the promising potentials of our leveling and sectoring technique